Evaluation of Crossbred Heifer Calves Rearing Practices and Growth Performace in Urban and Peri-Urban Dairy Systems of Sebeta Awas Wereda, Oromia, Ethiopia - Shibru, Dereje; Mekasha, Yoseph (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The study was aimed at evaluating the rearing practice and growth performance of heifer calves in urban and peri-urban dairy systems of Sebeta Awas Wereda, Oromia National Regional State, Ethiopia. Stratified random sampling method was used to select target farms and sample respondents for the prepared questionnaire. Farms for monitoring study was selected from data collected during the survey. Hence, 18 farms which had crossbred dairy heifer calves of (3-6 months of age), were purposively selected from both production systems and across the entire herd size category. Eighteen heifer calves were monitored from 18 different farms (2 production systems, 3 farm sizes, 3 replicates). Dairy farming has been gradually expanding in the area through years where above 90% of farms were established within last fifteen years. The overall average crossbred dairy herd size per household was 10.6±2.1 in urban and 11.3±2 in peri-urban area, where, the proportion of heifers accounted for 50.5% for urban and 48.8% for peri-urban farms of their respective total herds. Stall-feeding system is commonly practiced in urban and peri-urban farms, mostly feeding hay, straw, high-energy and protein feeds. Above 91.7% households raised their heifer calves through bucket feeding, where, 60%, 26% and 14% of overall farms weaned their calves at three, four and above four months of age respectively. Crude protein (CP) to metabolizable energy (ME) ratio of offered feeds to heifer calves were slightly below the desired level (66:1) in most farms. Body weight change, body condition score, girth height and average daily body weight gain (adg) of heifer calves were not affected by production systems. There was significant difference in body weight changes and adg due to difference in herd sizes. The overall observed heifer calf rearing and growth were good. But relatively inferior performance and prominent management problems were observed in medium sized farms Key words: heifer calf, urban, peri-urban, body weight, body condition score Abstrak. Penelitian ini bertujuan mengevaluasi praktik budidaya dan pertumbuhan sapi heifer di peternakan kota dan pinggir kota di Sebeta Awas Wereda, Oromia National Regional State, Ethiopia. Metode sample acak terstruktur digunakan untuk memilih target peternakan dan sampel responden untuk kuesioner. Peternakan untuk penelitian dipilih dari data yang dikumpulkan selama survei, sehingga ada 18 peternakan dengan sapi heifer perah silang berusia 3-6 bulan dipilih baik dari segi sistem produksi dan dari seluruh kategory jumlah ternak. Delapan belas sapi heifer diteliti dari 18 peternakan berbeda (2 sistem produksi, 3 ukuran peternakan, 3 pengulangan). Peternakan sapi perah berangsur berkembang di daerah itu sepanjang tahun dimana lebih dari 90% peternakan dibangun selama 15 tahun terakhir. Total rataan jumlah ternak sapi perah silang per rumah tangg adalah 10,6±2,1 di daerah kota dan 11,3±2 di pinggiran kota, dimana proporsi total ternak heifer sejumlah 50,5% di kota dan 48,85% di pinggiran kota. Sistem stall feeding umumnya diterapkan di peternakan kota dan pinggir kota yang sebagian besar menggunakan pakan jerami, rumput serta pakan tinggi protein dan energi. Lebih dari 97,6% rumah tangga memelihara ternaknya dengan pakan yang diberikan dalam ember, 60% peternakan memelihara ternak berumur 3 bulan, 26% empat bulan dan 14% diatas 4 bulan. Rasio protein kasar (PK) terhadap energi metabolit (ME) pada pakan berada di bawah level peternakan pada umumnya (66:1). Perubahan bobot tubuh, nilai kondisi tubuh, lingkar dada dan penambahan bobot tubuh harian (pbbh) sapi heifer tidak dipengaruhi oleh sistem produksi. Ada perbedaan nyata dalam perubahan bobot tubuh dan pbbh karena perbedaan jumlah ternak. Keseluruhan kondisi pemeliharaan dan pertumbuhan sapi heifer bagus, namun peternakan berukuran sedang menunjukkan performa yang kurang baik dan masalah manajemen yang menonjol. Kata kunci: sapi heifer, kota, pinggir kota, bobot tubuh, nilai kondisi tubuh